Statehood and governance: challenges in the Middle East and North Africa - Oliver Schlumberger (Deutsches Institut für Entwicklungspolitik (DIE), 2007)
Stagnant human and economic development in the Middle East and North Africa (MENA), from Iran to Morocco, is mainly due to systemic political factors. The durability of authoritarian rule in the region is based on non-democratic legitimacy (welfare benefits, ideology and tradition/religion). In addition, there is a powerful convergence of interests of external actors and those of Arab authoritarian regimes in the maintenance of the political status quo. State services therefore fall short of the region's development potential, while the monopoly of power is often abused by the state. As transitions of political systems make for instability and uncertainties, external actors should begin by seeking to increase the public scope for non-governmental actors, to integrate opposition groupings into the political system and to ensure that the monopoly of power is applied less repressively.
Keywords: 330